Does an x-autosome centric fusion in Acridoidea condemn the species to extinction? - Mesa, A. [UNESP]; Fontanetti, C. S. [UNESP]; García-Novo, P. [UNESP] (Pensoft Publishers, 2001)
Based on analysis of more than fifty species of neotropical grasshoppers with a neo XY sex determining mechanism, the authors suggest that species acquiring such mechanisms are finally extinct at the end of a relatively short evolutionary process.
Keywords: Acridoidea; Chromosomes; Grasshoppers; Sex determination; Species extinction